Stainless steel/polyester woven fabrics and copper/polyester woven fabrics: Manufacturing techniques and electromagnetic shielding effectiveness. (July 2016) - Lou, Ching-Wen; Lin, Ting An; Chen, An-Pang; Lin, Jia-Horng
This study uses metallic wires, stainless steel (SS) wires, and copper (Cu) wires as the core and 75 denier polyester (PET) fibers as the wrap material to form the metal/PET wrapped yarns. The optimal SS/PET and Cu/PET wrapped yarns are then made into different woven fabrics. The test results of the metallic wrapped yarns show that the optimal tenacity occurs with the wrapping count being 12 turns/cm, while the metal/PET woven fabrics have a low surface resistivity due to the conductive metal/PET wrapped yarns along the weft direction. An increasing number of laminating layers increases the electromagnetic shielding effectiveness (EMSE) while decreasing the air permeability of the woven fabrics. The laminating angle is also proportional to the EMSE of the woven fabrics. In sum, the combination of metal wires and PET fibers provides the resulting woven fabrics with good EMSE.